Study of the 3H(p,n)3He neutron producing reaction at N.C.S.R. “Demokritos” – Application on the 232Th(n,f) reaction - Gkatis, Georgios; Michalopoulou, Veatriki; Chasapoglou, Sotiris; Vlastou, Roza; Kokkoris, Mike; Axiotis, Mike; Lagoyannis, Anastasios (HNPS Advances in Nuclear Physics, 2022)
In the present work, the neutron beams produced via the 3H(p,n)3He reaction, were studied at N.C.S.R. “Demokritos”. For detecting and monitoring the neutrons, the following reference reactions 238U(n,f), 235U(n,f) and 237Np(n,f) were used. Furthermore, a systematic study of the parasitic neutrons, produced via reactions on the target constituents, was performed. At the same time, the cross sections of the 232Th(n,f) reaction were deduced, in the energy range from 2 to 5.5 MeV. Seven actinide targets were used, coupled with seven Micromegas detectors, one for each target, for the detection of the fission fragments. The target-detector assembly was placed in an aluminum chamber filled with Ar:CO2 (90:10) in atmospheric pressure and room temperature. Monte Carlo simulations with the MCNP6 code, coupled with the NeuSDesc and SRIM-2013 codes, were used for the estimation of the neutron beam incident at each target. Additional Monte Carlo simulations were carried out using the codes FLUKA and GEF, in order to determine the exact masses of the 232Th targets and the energy deposition of the fission fragments in the detector gas.